1998
DOI: 10.1136/jamia.1998.0050441
|View full text |Cite
|
Sign up to set email alerts
|

Arizona Telemedicine Program: Implementing a Statewide Health Care Network

Abstract: The Arizona Telemedicine Program was established in July 1996 by the Arizona state legislature. The organizational center for the program is the Arizona Health Sciences Center in Tucson. Key goals for the program include increased access to specialty services for rural, underserved populations; development of cost-effective telemedicine services; and expansion of opportunities for education of health professionals in rural areas. The program provides several levels of services based on both store-and-forward a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 4 publications
0
14
0
2
Order By: Relevance
“…[1][2][3][4] It has also been demonstrated that diagnostic performance with relatively low-resolution store-forward digital images (720 3 500 pixels) is equivalent to high-resolution images (1490 3 1000 pixels), making it possible to use a relatively modest camera configuration. 5 As a result of these feasibility studies, many programs, including our own, 6 are utilizing store-forward technologies for their teledermatology services. However, as noted in a recent review of teledermatology, there are still areas that need to be investigated to help ensure comparability of telemedicine services with in-person services.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] It has also been demonstrated that diagnostic performance with relatively low-resolution store-forward digital images (720 3 500 pixels) is equivalent to high-resolution images (1490 3 1000 pixels), making it possible to use a relatively modest camera configuration. 5 As a result of these feasibility studies, many programs, including our own, 6 are utilizing store-forward technologies for their teledermatology services. However, as noted in a recent review of teledermatology, there are still areas that need to be investigated to help ensure comparability of telemedicine services with in-person services.…”
Section: Introductionmentioning
confidence: 99%
“…In May of 1997 the Arizona Telemedicine Program (ATP) 17 started providing teleconsultations to rural sites in Arizona. Although the program currently has a number of interconnected sites on the network, this paper is only concerned with seven core sites that primarily send teleconsultation cases to the University of Arizona College of Medicine hub site.…”
Section: Methodsmentioning
confidence: 99%
“…The Arizona Telemedicine Program (ATP) 13 began providing teleconsults in May of 1997 (May 2, 1997 was the first consult). In addition to the patients' medical records, detailed data including demographics and case turn-around times 3 are collected and analyzed.…”
Section: Methodsmentioning
confidence: 99%